Kfri in Western writing and works - Ahmed, Prof. Dr. Saman Hussein; Sabir, Asst. L. Dilman Mohammad (Sulaimani Journal for Humanities, 2025)
Reflection on the observations and views of the Eastern and the journey of important sources in Kurdish history The person started this research by researching in the interest of the journey that Zarwa area, the city of Kafri and how you talk about it in their books, and what is the reasons mentioned in it Talk Al-Kitabat, and your research in the important field of coldness that went to Talk Al-Kitabat in the restoration of the historical reality of the city in Talk Al-Fitr, and you using the descriptive method Analysis and reliance on the original sources for their own situation and their comparison with their contemporary sources, especially Ottoman calendars and documents, and the most important sources that have come Therefore, the main reason for visiting a large number of travelers to the country is that it is one of the main trade routes between Mosul, Baghdad, Baghdad and Sulaymaniyah Therefore, the children of the town of Kafri do not travel in the area, but some of them settled in the town to learn and advance to the news about the monuments, history, lifestyle and culture Scanning development for the country.
Keywords: kfri; Flames; Social Life; Geography; Urban Aspects